Peranan Sistem Informasi Komputer Dalam Evolusi Bisnis Ke Era Digital 5.0 - Abdul Sakti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of information technology has significantly impacted the evolution of business into the digital era 5.0. In this context, the role of Computer Information Systems (CIS) becomes crucial in facing the challenges and opportunities that arise. This study aims to explore the role of CIS in Business 5.0, focusing on technology integration and business processes, analytical capabilities and data-driven decision-making, automation and operational efficiency, information security and compliance, as well as accountability and transparency. The research methodology involved literature search from academic databases and scientific journals using relevant keywords such as